Effectiveness of Pharmacological Intervention Among Men with Infertility: A Systematic Review and Network Meta-Analysis - Muhammad Nabeel Shahid; Muhammad Nabeel Shahid; Tahir Mehmood Khan; Tahir Mehmood Khan; Chin Fen Neoh; Qi Ying Lean; Qi Ying Lean; Allah Bukhsh; Allah Bukhsh; Mahmathi Karuppannan (Frontiers Media S.A., 2021)
Background. Infertility is an emerging health issue for men. Comparative efficacy of different pharmacological interventions on male infertility is not clear. The aim of this review is to investigate the efficacy of various pharmacological interventions among men with idiopathic male infertility. All randomized control trials evaluating the effectuality of interventions on male infertility were included for network meta-analysis (NMA) from inception to 31 April 2020, systematically performed using STATA through the random effect model. The protocol was registered at PROSPERO (CRD42020152891).Results. The outcomes of interest were semen and hormonal parameters. Treatment effects (p < 0.05) were estimated through WMD at the confidence interval of 95%. Upon applying exclusion criteria, n=28 RCTs were found eligible for NMA. Results from NMA indicated that consumption of supplements increases sperm concentration levels [6.26, 95% CI 3.32, 9.21] in comparison to SERMs [4.97, 95% CI 1.61, 8.32], hormones [4.14, 95% CI 1.83, 6.46], and vitamins [0.15, 95% CI −20.86, 21.15)] with placebo, whereas the use of SERMs increased percentage sperm motility [6.69, 95% CI 2.38, 10.99] in comparison to supplements [6.46, 95% CI 2.57, 10.06], hormones [3.47, 95% CI 0.40, 6.54], and vitamins [−1.24, 95% CI −11.84, 9.43] with placebo. Consumption of hormones increased the sperm morphology [3.71, 95% CI, 1.34, 6.07] in contrast to supplements [2.22, 95% CI 0.12, 4.55], SERMs [2.21, 95% CI −0.78, 5.20], and vitamins [0.51, 95% CI −3.60, 4.62] with placebo. Supplements boosted the total testosterone levels [2.70, 95% CI 1.34, 4.07] in comparison to SERMs [1.83, 95% CI 1.16, 2.50], hormones [0.40, 95% CI −0.49, 1.29], and vitamins [−0.70, 95% CI −6.71, 5.31] with placebo. SERMs increase the serum FSH levels [3.63, 95% CI 1.48, 5.79] better than hormones [1.29, 95% CI −0.79, 3.36], vitamins [0.03, 95% CI −2.69, 2.76], and supplements [−4.45, 95% CI −7.15, −1.76] in comparison with placebo.Conclusion. This review establishes that all interventions had a significantly positive effect on male infertility. Statistically significant increased sperm parameters were noted in combinations of zinc sulfate (220 mg BID), clomiphene citrate (50 mg BID), and testosterone undecanoate and CoQ10; tamoxifen citrate and FSH were shown to improve the hormonal profile in infertile males.